DENTINAL WALL ADAPTATION OF THERMOPLASTICIZED GUTTA-PERCHA IN THE ABSENCE OR PRESENCE OF SMEAR LAYER - A SCANNING ELECTRON-MICROSCOPIC STUDY - (:unkn) unknown (WILLIAMS & WILKINS, 1993)
The dentinal adaptation of injected thermoplasticized gutta-percha and thermoplasticized gutta-percha resulting from Ultrafil and Thermafil systems was evaluated by scanning electron microscopy and compared with adaptation obtained with the lateral condensation of gutta-percha. Each method was evaluated with and without the smear layer removed. Scanning electron microscopic observations showed the thermoplasticized gutta-percha resulting from either system to have better dentinal wall adaptation than lateral condensation of gutta-percha in either the absence or presence of the smear layer. In the absence of smear layer, the adaptation of gutta-percha was improved in all groups. Although sealer was used, removing the smear layer was found to enhance the ability of the thermoplasticized gutta-percha to enter the patent tubules.
Keywords: PENETRATION